Uncovering the sports livestreaming platform value co-creation process - Liu, Haoyu (2023)
Sport Livestreaming Platforms (SLSPs) have emerged as a new paradigm, offering a synchronised, interactive experience to sports enthusiasts. Despite their popularity, little is known about the processes through which viewers co-create value with service providers during their engagement on these platforms. More specifically, there are several research gaps: 1) empirical research using mixed methods on the value co-creation process at SLSPs is scarce; 2) the typology of SLSP viewer engagement behaviour is vaguely described in previous studies; 3) there is a lack of a comprehensive value co-creation model that explains how value is co-created by viewers with other actors on SLSPs; 4) a validated measurement scale, specifically tailored for evaluating the value co-creation process within the context of SLSPs, is notably absent. These research gaps lie in the understanding of how diverse viewers interact with various actors to derive value through their engagement experiences on SLSPs. The gaps are significant as the insights derived from studies could greatly assist firms running SLSPs to tailor their services more effectively, further enhancing user experience and engagement. This research addresses these research gaps by using a mixed-method design and single case studies to investigate four key areas: (1) classifying sport viewers based on their engagement behaviours on SLSPs; (2) proposing a Value-in-Engagement Experience Process (VEEP) model; (3) developing a valid measurement scale for VEEP on SLSPs, and (4) testing the model and identifying the value co-creation process across various viewer groups on SLSPs.